KONSENTRASI ANDALIMAN SEBAGAI DAYA PENOLAKAN NYAMUK SEBAGAI VEKTOR PENYAKIT MENULAR DI KABANJAHE - Nurmala Hayati Sihombing; Susanti Br. Perangin-angin (Poltekkes Kemenkes Medan, 2024)
Andaliman plant (Zanthoxylum acanthopodium) is one of the plants in the province of Sumatera Utara. Andaliman fruit have antioxidant activity, larvacide, analgesic, antimicrobial, and antifungal besides for maintain the color and aroma of food (Ginting et al., 2022). The compounds were flavanoid, saponin, alkaloid, and tannin, where be use cost-effective environment safety. This study aims to determine of protective power fruit andaliman extract as a natural repellent at concentrations 20 gr, 40 gr and 60 gr. The benefits is to determine the protective power of fruit andaliman extract as a repellent, so it can be input for the community and health services in efforts to control infectious diseases by mosquitoes. The research method is experimental (laboratory experiment) with control .The experimental and control groups are compared. The population was all mosquitoes. Sample was 100 mosquitoes for three repetitions; 20 gr, 40 gr and 60 gr of Andaliman fruit extract. Before becoming adult, researchers bred mosquitoes from larvae and provided containers and maintained them until they became adult. Data analysis using One way ANOVA test was conducted to determine whether there was a difference in the effect of each concentration. The results of the study show there is an effect of differences of protective power in each concentration of andaliman extract (p-value=0.000). If sorted from highest to lowest protective power are 60 gr 9 minutes, 60 gr 6 minutes, 40 gr 9 minutes, 60 gr 3 minutes, 20 gr 9 minutes, 40 gr 3 minutes, 40 gr 6 minutes, 20 gr 6 minutes and 20 gr 3 minutes. The results, fruit andaliman extract can be used as a basic igredient repellents, but further research is still needed on the content of the active substances, allergic reactions and sensitivity to skin.